You should use the following substitution to solve the given integral such that:

`sin x = t => cos x dx = dt`

Changing the variable yields:

`int cos x*sin(sin x)dx = int sin t dt`

`int sin t dt = -cos t + c`

Substituting back `sin x` for `t` yields:

`int cos x*sin(sin x)dx = - cos(sin x) + c`

You may evaluate the definite integral using fundamental theoem of calculus such that:

`int_(x_1)^(x_2) f(x) dx = F(x_2) - F(x_1)`

Reasoning by analogy yields:

`int_0^(pi/4) cos x*sin(sin x)dx = - cos(sin x)|_0^(pi/4)`

`int_0^(pi/4) cos x*sin(sin x)dx = - cos(sin (pi/4)) + cos(sin 0)`

`int_0^(pi/4) cos x*sin(sin x)dx = - cos(sqrt2/2) + cos 0`

**Hence, evaluating the given definite integral yields `int_0^(pi/4) cos x*sin(sin x)dx = cos 0 - cos(sqrt2/2). ` **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now